Perbedaan Harga Saham Sebelum dan Setelah Stock Split Studi Empiris Pada Perusahaan Yang Melakukan Stock Split Pada Tahun 2016-2020 - Dewita Rizma Amirezy; Jeni Susyanti; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine and analyze the difference in stock prices before and after the stock split, empirical studies on companies that carry out stock splits in 2016-2020.This research is a type of event study research, using a quantitative approach or positivism. The analytical method used is descriptive statistics in the form of mean and standard deviation. The sample used in this study amounted to 27 companies.The results of this study indicate that there is a significant difference between stock prices before and after the stock split. Thus it can be concluded that the stock split has an effect on the company's stock price. Keywords : Before, After Stock Split and Stock Price